2018
DOI: 10.1007/s11101-018-9595-8
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the biosynthesis of esterified oxylipins and their involvement in plant defense and developmental mechanisms

Abstract: Plant oxylipins produced following oxidation of unsaturated fatty acids are structurally diverse metabolites that play crucial developmental and defensive roles. Whereas free oxylipins are well studied, oxylipins esterified in complex lipids such as galacto-and phospholipids are thought to be rare and have unclear roles. In the last few years, new analytical methods have been developed, leading to the discovery of many esterified oxylipins in a variety of plant species. This suggests that these molecules may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 100 publications
(213 reference statements)
0
34
0
Order By: Relevance
“…Certain undesired microbe interaction with plant host produced hypersensitive response which can be determined by the production of hypersensitive inducing molecules in plants (Terrón-Camero et al, 2018). We quantified two intracellular signalling molecules for inducing HR (c-di-GMP (Terrón-Camero et al, 2018) and cAMP level (Almblad et al, 2019) and four metabolites (phosphatidic acid (PA) pure Oxo-phytodeinoic acid (OPDA), esterified OPDA, and Jasmonic acid (JA) in maize seedlings through GC/MS technique (Genva et al, 2019). Result deducted that under uniconizole treatment, the concentration of these hypersensitive molecules was same as control (Figure 5A-5J & 6A-6T).…”
Section: Resultsmentioning
confidence: 99%
“…Certain undesired microbe interaction with plant host produced hypersensitive response which can be determined by the production of hypersensitive inducing molecules in plants (Terrón-Camero et al, 2018). We quantified two intracellular signalling molecules for inducing HR (c-di-GMP (Terrón-Camero et al, 2018) and cAMP level (Almblad et al, 2019) and four metabolites (phosphatidic acid (PA) pure Oxo-phytodeinoic acid (OPDA), esterified OPDA, and Jasmonic acid (JA) in maize seedlings through GC/MS technique (Genva et al, 2019). Result deducted that under uniconizole treatment, the concentration of these hypersensitive molecules was same as control (Figure 5A-5J & 6A-6T).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, OPDA is also found esterified to galactolipids (8,9). However, it has not been entirely clarified whether esterified oxylipins are produced from free fatty acid intermediates or whether synthesis can occur on fatty acids while they are esterified into lipids (10).…”
mentioning
confidence: 99%
“…Following biotic and abiotic stress, lipids can release FFAs (including free saturated fatty acids and free unsaturated fatty acids), and then the FFAs can be oxidized into a wide range of metabolites. The lipids can also be directly oxidized into oxylipin-containing lipids (Genva et al 2018). In this study, the total amount of oxylipincontaining glycolipids (MGDGs and DGDGs) and oxylipin-containing PGs increased at 1 h after treatment with oligochitosan; however, glycolipids (MGDGs), PGs, and FFAs (C14:0, C16:0, C16:2, C16:3, C18:0, C18:2 and C18:3) decreased at the same time.…”
Section: Discussionmentioning
confidence: 56%
“…The results suggested that the synthesized glycerolipids were oxidized to oxylipin-containing glycerolipids, rather than they released FFAs in response to oligochitosan treatment. Plants produced high amount of oxylipin-containing lipids under stress conditions (Genva et al 2018). Buseman et al (2006) found that the content of oxylipin-containing lipids (glycerolipids containing oxophytodienoic acid and dinor-oxophytodienoic acid) was higher in Arabidopsis wounded leaves than in control ones.…”
Section: Discussionmentioning
confidence: 99%